EVALUASI UJI KLON JATI (Tectona grandis L.f) UMUR 3,5 TAHUN DI HUTAN PENDIDIKAN WANAGAMA GUNUNG KIDUL - , wahid nurrudin ([Yogyakarta] : Universitas Gadjah Mada, 2013)
on 10 Clonal test 0 clones of 3,5 years old teak (Tectona grandis L.f) was evaluated. Clonal test of Jati Unggul Nusantara (JUN) has been planted with randomized completely block design in Compartment 14 Wanagama Gunung Kidul which has thin soil depth. Clonal test was conducted to select and obtain superior clones in order to increase the productivity of teak clonal forestry. The height and diameter growth of the trees were observed every 2 months, along with the measurement of diameter growth in Î¼m scale, soil depth, soil humidity, and weather. Mortality rate, height (T), and diameter (D) highly varied among clones in the population. Clone heritability increased gradually with age. Clone heritability for T (H 2 =0,47) was lower than D (H 2 =0,51) after 3,5 years old. Meanwhile, genetic correlation between height and diameter growth was 0,95. High level of heritability showed that the growth of clonal test population was strongly controlled by genetic factor. Population growth was also significantly affected by the interaction between clone and environment. Overall, rainfall and soil depth are abiotic factors that influence teak growth in Wanagama. Although abiotic environmental factors might influence the variation of clone growth, genetic factor affects the variation stronger. These results suggest that the growth of teak clonal test in Wanagama tends to be more affected by genetic factor than by abiotic environmental factors.